2020
DOI: 10.1371/journal.ppat.1008319
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 regulates mitochondrial function and immune homeostasis in respiratory syncytial virus infected dendritic cells

Abstract: Respiratory syncytial virus (RSV) is the major cause of lower respiratory tract infection in children worldwide. Sirtuin 1 (SIRT1), a NAD+ dependent deacetylase, has been associated with induction of autophagy, reprogramming cellular metabolism, and regulating immune mediators. In this study, we investigated the role of SIRT1 in bone marrow dendritic cell (BMDC) function during RSV infection. SIRT1 deficient (SIRT1-/-) BMDC showed a defect in mitochondrial membrane potential (Δ⍦m) that worsens during RSV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 64 publications
2
58
0
2
Order By: Relevance
“…37 Alterations in the levels and effects of cytosolic, nuclear, and mitochondrial sirtuins are also evident in a number of viral infections, including within dendritic cells, which have an important role in regulating the patterned immune response. 38 Generally, the sirtuins seem to be evolutionary conserved antiviral agents. 39 Like the circadian rhythm, viruses may act to disengage sirtuins from their regular physiological processes.…”
Section: Circadian Rhythm and Mitochondrial Metabolismmentioning
confidence: 99%
“…37 Alterations in the levels and effects of cytosolic, nuclear, and mitochondrial sirtuins are also evident in a number of viral infections, including within dendritic cells, which have an important role in regulating the patterned immune response. 38 Generally, the sirtuins seem to be evolutionary conserved antiviral agents. 39 Like the circadian rhythm, viruses may act to disengage sirtuins from their regular physiological processes.…”
Section: Circadian Rhythm and Mitochondrial Metabolismmentioning
confidence: 99%
“…Acetyl-CoA carboxylase (ACC) leads to the irreversible carboxylation of acetyl-CoA, with AhR activation increasing ACC via Synphilin-1 degradation [ 78 ]. The suppression of sirtuin-1 in dendritic cells also increases ACC levels and decreases acetyl-CoA, with consequent alterations in mitochondrial metabolism that lead to dendritic cells inducing deficient anti-viral responses [ 79 ]. ACC blockade in this study led to dendritic cell metabolic reprogramming that ameliorated mitochondrial dysfunction and restored a more appropriate anti-viral response [ 79 ].…”
Section: Ahr and Wider Covid-19 Pathophysiologymentioning
confidence: 99%
“…The suppression of sirtuin-1 in dendritic cells also increases ACC levels and decreases acetyl-CoA, with consequent alterations in mitochondrial metabolism that lead to dendritic cells inducing deficient anti-viral responses [ 79 ]. ACC blockade in this study led to dendritic cell metabolic reprogramming that ameliorated mitochondrial dysfunction and restored a more appropriate anti-viral response [ 79 ]. Such data highlights the important role that acetyl-CoA and its regulation by ACC have in determining and fine-tuning mitochondrial function [ 80 ], and the impact that alterations in mitochondrial function have on the immune regulatory responses of dendritic cells.…”
Section: Ahr and Wider Covid-19 Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that loss of SIRT1 further induced mRNA expression of IL-17 in an animal model of RSV infection [ 128 ]. According to their considerations, SIRT1-deficient bone marrow dendritic cells elevated Acetyl CoA carboxylase 1 (ACC1), which is associated with fatty acid synthesis, resulting in the activation of an abnormal metabolic process, which in turn preceded an excessive virus-induced immune response [ 128 ]. In other words, SIRT1 may regulate the Th17 immune response from virus-infected dendritic cells by regulating their metabolic pathways [ 128 ].…”
Section: The Role Of Sirt1 In Inflammatory Cellsmentioning
confidence: 99%